(untitled) (Jurnal Ekonomi dan Manajemen, 2025)
This study aims to analyze the effect of service quality and tax sanctions on taxpayers’ motivation and its impact on compliance in paying Land and Building Tax (PBB). The research employs a quantitative approach using a survey technique. Data were collected through questionnaires distributed to 100 taxpayer respondents at the Regional Tax Service Agency of Malang City. The data were analyzed using path analysis to examine direct and indirect relationships among variables. The findings reveal that service quality significantly influences taxpayers’ motivation but does not directly affect tax compliance. Conversely, tax sanctions do not significantly affect taxpayers’ motivation but have a direct impact on tax compliance. Additionally, taxpayer motivation acts as a mediating variable in the relationship between service quality, tax sanctions, and tax compliance. These findings suggest that improving tax compliance can be achieved through a combination of enhanced service quality, strict enforcement of tax sanctions, and strategies to increase taxpayers’ motivation.